An exploratory study of~the~concept of social procurement in~the construction industry in~Botswana: Contractor's perspective - Joseph Kuruneri; Wiston Zivanai (Modern Supply Chain Research and Applications, 2024)
Purpose - Governments worldwide seek to optimize value in public project bids. Social procurement (SP) has become a global tool for achieving project goals. The purpose of this study is to assess the understanding of SP among contractors and identify its drivers to optimize the value associated with public projects. Design/methodology/approach - A total of 15 major contractors were interviewed to obtain their views on SP, appreciate their current practices and identify the main drivers of SP in projects. A semistructured interview was used to gather relevant data. Neo-institutional theory is the lens of the study used to provide the focus of the research. The collected data were analyzed using the thematic data analysis technique. Findings - The study found that SP is understood as corporate social responsibility and is not handled in a structured manner guided by policies or clearly defined procedures. Additionally, research has shown that compliance requirements, rather than value and goodwill, are the main inspiration for SP practices. Research limitations/implications - The study's limitation is the fact that it was conducted in the context of Botswana and only used the interview technique as the solo data collection method. The other limitation is the lack of empirical literature on SP concerning the lack of SP policy in Botswana. Originality/value - This study raises awareness of the concept of SP among contractors in Botswana and eases its implementation within the industry.
Keywords: 650; Construction; Contractor; Institutional theory; Social procurement; Social value; Sustainability